Retrospective Analysis of Pregnancy Terminations: 9-Years Experience at a Tertiary Hospital in Southeastern Turkey - Neslihan Bayramoglu Tepe; Reyhan Gunduz; Omer Faruk Dizibuyuk; Huseyin Caglayan Ozcan; Ozge Komurcu Karuserci; Seyhun Sucu; Tanyeli Guneyligil Kazaz; Ali Irfan Kutlar (Gynecology Obstetrics & Reproductive Medicine)
Objective: To determine the indications for termination of pregnancy, and their consistency with autopsy data to offer an insight into termination of pregnancy having regard to conditions in Turkey.